2008
DOI: 10.1111/j.1600-0404.2007.00953.x
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of etiologies in patients above and below age 45 with first-ever ischemic stroke

Abstract: In stroke patients below the age of 45, the TOAST classification should be expanded to better classify the wide diversity of stroke etiologies. The relatively low frequency of routine stroke etiologies in patients aged < or = 45 can be explained by the significantly lower prevalence of traditional risk factors in these patients. In patients 46-60 years old, the TOAST classification is adequate in the characterization of ischemic stroke etiologies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
19
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 30 publications
1
19
2
Order By: Relevance
“…These have suggested sex differences in risk factor distribution 4 -7 and higher frequencies of vascular risk factors in older age groups of young adult patients with stroke. 4,[7][8][9][10][11][12] Particularly in young adults, sex-and age-specific differences have awaited investigations on a larger scale, for instance, to gather more generalizable and usable information for young-onset stroke prevention.…”
mentioning
confidence: 99%
“…These have suggested sex differences in risk factor distribution 4 -7 and higher frequencies of vascular risk factors in older age groups of young adult patients with stroke. 4,[7][8][9][10][11][12] Particularly in young adults, sex-and age-specific differences have awaited investigations on a larger scale, for instance, to gather more generalizable and usable information for young-onset stroke prevention.…”
mentioning
confidence: 99%
“…Only just reports from 2002 to 2012 years have shown a great diversity in TOAST subtypes in young IS patients ( Table 5) [26][27][28][29][30][31][32][33][34][35][36][37][38][39]. In addition to differences in research design, areas, composition and sources of patients, sample size, and other factors, it was assumed that this diversity also may be due to the fact that the aetiology of young stroke is more complex than that of elderly patients and that the TOAST classification is not suitable for young stroke [40]. A previous study showed that nontraditional causes including dissections and thrombophilias were the most frequent in distribution of aetiologies by TOAST in young IS [40].…”
Section: Subtype Constituents Of Ismentioning
confidence: 99%
“…In addition to differences in research design, areas, composition and sources of patients, sample size, and other factors, it was assumed that this diversity also may be due to the fact that the aetiology of young stroke is more complex than that of elderly patients and that the TOAST classification is not suitable for young stroke [40]. A previous study showed that nontraditional causes including dissections and thrombophilias were the most frequent in distribution of aetiologies by TOAST in young IS [40]. Another study on IS of unusual cause enrolled 70 patients and showed hematological disorders in 17 cases, infection in 11, migraine stroke in 10, cerebral infarction secondary to venous thrombosis in 9, primary inflammatory vascular conditions in 6 and miscellaneous causes in 17, and an age of 45 years or less was one of independent predictors of the stroke [41].…”
Section: Subtype Constituents Of Ismentioning
confidence: 99%
“…Onset time was defined as the first appearance of abnormal signs that were noticed by the treating team in the intensive care unit or in the cardiothoracic-surgery department. Ischemic strokes and intracerebral hemorrhages were differentiated by the findings on brain CT, performed in all patients between days 1 and 8 after stroke onset since MRI is not routinely performed for assessment of stroke in Israel [11,12]. Ischemic stroke etiology was determined using the TOAST classification [13,14].…”
Section: Methodsmentioning
confidence: 99%